Older patients' autonomy when cared for at emergency departments. (August 2022) - Frank, Catharina; Holmberg, Mats; Jernby, Elin Ekestubbe; Hansen, Annika Sevandersson; Bremer, Anders
Background: Older patients in emergency care often have complex needs and may have limited ability to make their voices heard. Hence, there are ethical challenges for healthcare professionals in establishing a trustful relationship to determine the patient's preferences and then decide and act based on these preferences. With this comes further challenges regarding how the patient's autonomy can be protected and promoted. Aim: To describe nurses' experiences of dealing with older patients' autonomy when cared for in emergency departments (EDs). Research design: This study adopted reflective lifeworld theory and a phenomenological design. Participants and research context: A total of 13 open-ended interviews were performed with nurses working at two EDs in Sweden. Ethical considerations: The study was reviewed by the Ethical Advisory Board in South East Sweden and conducted according to the Declaration of Helsinki. All participants gave consent. Findings: Nurses' experiences of dealing with older patients' autonomy in EDs are characterized by moving in a conflicting uphill struggle, indicating obscure thoughts on how patient autonomy can be protected in an ethically challenging context. The phenomenon is further described with its meaning constituents: 'Being hampered by prioritization under stress', 'Balancing paternalism and patient autonomy', 'Making decisions without consent in the patient's best interests' and 'Being trapped by notions of legitimate care needs'. Conclusion: Stressful work conditions and lacking organizational strategies in EDs contribute to nurses maintaining unjustified paternalistic care, regardless of the patient's ability and medical condition, and questioning who has legitimacy for participating in decisions about care. The nurses' protection and promotion of older patients' autonomy is dependent on the opportunity, ability and willingness to create a patient relationship where the patient's voice and preferences are valued as important. Consequently, strategies are needed to improve patient autonomy in EDs based on the idea of 'relational autonomy'.